Soil microbial properties as influenced by agri-silvi-horticultural system under semi-arid region of Haryana - DEVI, SONIA; BHARDWAJ, K K; DAHIYA, GARIMA; SHARMA, M K; DHILLON, R S; DEVI, PRIYANKA (The Indian Journal of Agricultural Sciences, 2021)
The study was carried out at Forestry Research Farm, CCSHAU, Hisar to assess the effect of agri-silvi-horticulturalsystem, i.e. on different soil microbial properties. Surface soil (0–15 cm) samples were collected randomly and thenthese samples were immediately used for analyzing potentially mineralizable nitrogen, microbial biomass carbon,dehydrogenase activity, alkaline phosphatase activity and urease activity under 3 treatments (5 replications), i.e. control(wheat), Kinnow + wheat and Kinnow + Eucalyptus + wheat. Significant improvement in soil biological propertieswas observed under tree-based system as all biological properties were recorded highest in Kinnow + Eucalyptus +wheat system followed by Kinnow + wheat as compared to control. Dehydrogenase and alkaline phosphatase activitywere higher under Kinnow + Eucalyptus + wheat (69.3 and 33.8%) followed by Kinnow + wheat (39.6 and 12.2%)over control. Similarly, microbial biomass carbon (MBC) and urease activity were observed to be higher under Kinnow+ Eucalyptus + wheat (50.3 and 31.9%) followed by Kinnow + wheat (28.9 and 12.3%) over control. A linearpositive regression relationship was observed among organic carbon vs. microbial biomass carbon. The coefficientof determination for organic carbon and microbial biomass carbon explained variability of 98.3%. The result of thestudy showed that tree-based agroforestry system can significantly increase the soil biological properties. Based onthe present study, it was suggested that soil microbiological activities can be enhanced by adopting agroforestry ortree-based system.